2014
DOI: 10.1002/prep.201300198
|View full text |Cite
|
Sign up to set email alerts
|

Calculation of Decomposition Products from Components of Gunpowder by using ReaxFF Reactive Force Field Molecular Dynamics and Thermodynamic Calculations of Equilibrium Composition

Abstract: The major combustion products from munitions containing nitro‐based propellants are water, carbon monoxide, carbon dioxide, hydrogen, and nitrogen. In addition, compounds including hydrogen cyanide, ammonia, methane, nitrogen oxides, benzene, acrylonitrile, toluene, furan, aromatic amines, benzopyrene, and various polycyclic aromatic hydrocarbons are detected in minor concentrations. The literature shows that the thermodynamic prediction of the major decomposition products agrees fairly well with the measureme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Of further note, low combustion temperature formulations which use such polymeric ingredients (e.g., smoke formulations) may produce more of these VOCs than other higher combustion temperature formulations . Thus, it may be concluded that these calculations are useful but inadequate when considering these nonequilibrium products, such as volatile organic compounds (VOCs), which are known to be produced via the thermal degradation of common polymeric ingredients in pyrotechnic compositions …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of further note, low combustion temperature formulations which use such polymeric ingredients (e.g., smoke formulations) may produce more of these VOCs than other higher combustion temperature formulations . Thus, it may be concluded that these calculations are useful but inadequate when considering these nonequilibrium products, such as volatile organic compounds (VOCs), which are known to be produced via the thermal degradation of common polymeric ingredients in pyrotechnic compositions …”
Section: Discussionmentioning
confidence: 99%
“…42 Thus, it may be concluded that these calculations are useful but inadequate when considering these nonequilibrium products, such as volatile organic compounds (VOCs), which are known to be produced via the thermal degradation of common polymeric ingredients in pyrotechnic compositions. 43 It is clear that a tremendous molecular diversity results from the thermal degradation of polymeric materials within a pyrotechnic reaction. This work demonstrates that new pyrotechnic development should consider utilizing analytical techniques that can capture and assess new byproducts that are…”
Section: ■ Conclusionmentioning
confidence: 99%
“…Then we adopted the ReaxFF force field for molecular dynamics simulations. 30 The system is first heated to 300 K with repeated velocity rescaling methods and then followed by a 10 ps NVE molecular simulations. 31 The time step and the total simulation time are 0.1 fs and 10 ps respectively.…”
Section: Methodsmentioning
confidence: 99%
“…For the same AP/HTPB system, three different reaction mechanisms have been proposed and simulated, which are based on the global chemistry using symbolic species for the three flames, a 12-species mechanism, and a 72-step reaction mechanism with 39-species, respectively [11]. Except for the numerical simulations, the chemical structure of the propellant flame could be predicted by ReaxFF reactive force field molecular dynamics and equilibrium thermodynamics simulations [12]. It has been found that the ReaxFF agrees considerably better with experimental results for minor species than the thermodynamic simulations.…”
Section: Introductionmentioning
confidence: 99%